Identification of Stress-Related Genes and a Comparative Analysis of the Amino Acid Compositions of Translated Coding Sequences Based on Draft Genome Sequences of Antarctic Yeasts - Baeza, Marcelo; Zúñiga, Sergio; Peragallo, Vicente; Barahona, Salvador; Alcaino, Jennifer; Cifuentes, Víctor (Frontiers in Microbiology, 2021)
The genomes of Antarctic yeasts were sequenced and employed to characterize the adaptations and responses of the yeasts that enable them to thrive in cold environments. Sequencing was performed using an Illumina HiSeq 4000 system, and the coding sequences were predicted by Augustus and annotated and classified according to predicted cellular function and subcellular localization. Yeasts were compared according to their growth parameters and the properties of putative proteins concerning their amino acid contents, flexibility indexes and dipeptide contributions to protein thermostability. The sizes of the draft genomes that were obtained ranged from 15 to 34 Mb, and the GC contents ranged from 29 to 61%. Putative genes related to various kinds of stress were identified and were especially numerous for the responses to oxidative and cold stress. Secondary metabolite clusters were predicted in all investigated yeasts, including the type III polyketide synthases in Candida sake and Cryptococcus sp., which have rarely been described in yeasts and fungi. In several groups of proteins, correlations were observed between their contents of flexible amino acids and both the yeasts' optimal temperatures for growth and their growth rates. In general, the contents of flexible amino acids were higher in yeasts growing more rapidly, as their optimal temperature for growth was lower, and the contents of flexible amino acids became lower among yeasts with higher optimal temperatures for growth as their growth rates increased.